A revised infrageneric classification of Bellevalia Lapeyr. (Asparagaceae: Scilloideae) based on molecular analysis - Jafari, Azarnoosh; Vaezi, Jamil; Forghanifard, Mohammad Mahdi; Forest, Félix; Manning, John C. (Phytotaxa, 2021)
Within the genus Bellevalia (Asparagaceae: Scilloideae: Hyacintheae), flower shape and colour, the ratio of leaf to scape length, and the orientation of the pedicels were traditionally used to delimit sections, subsections and species. We conducted a phylogenetic analysis of representative species from sections Bellevalia, Conicae, Nutantes and Oxydontae, representing four out of the six sections that are currently recognised, using the four chloroplast regions rbcL, matK, trnL intron, and trnL-F spacer. Our results indicate that the sections are not monophyletic as currently circumscribed. Our analyses retrieve two major, well-supported clades. The first clade (sect. Conicae) includes only species with ciliate leaves and green-veined perianth lobes, and the second clade (sect. Bellevalia) includes the species lacking these characteristics. Within the second clade, the species with yellow anthers are separated from those with violet anthers. Our molecular analysis does not support the traditional subdivisions of the genus but establishes the value of cilia on the leaf margin, green veins in the perianths lobes, and the colour of the anthers as indicators of relationships among the species. We recommend that the current four sections and six subsections of Bellevalia be reduced to two sections without subsections and we provide an updated and corrected nomenclature for these sections and subsections, designating lectotypes where necessary.